Small intestinal bacterial overgrowth in variant transthyretin amyloidosis (A-ATTRv) - Ana Moreno García; Mireia Grimalt Oliver; Juan González-Moreno; María Antonia Ribot-Sansó; Eugenia Cisneros-Barroso; Inés Losada López (Orphanet Journal of Rare Diseases)
Abstract Variant transthyretin amyloidosis (A-ATTRv) can lead to sensory, motor, and autonomic neuropathy, as well as a variety of gastrointestinal (GI) disorders. While previous studies have explored gastrointestinal symptoms in A-ATTRv, no studies have definitively examined the role of bacterial overgrowth, such as SIBO, in exacerbating these symptoms. Identifying the presence of SIBO in A-ATTRv patients could lead to better-targeted treatments for gastrointestinal complications. We conducted a cross-sectional, unicentric observational pilot study, analysing the presence of SIBO using a lactitol breath test in 39 individuals carrying the V30M mutation: 21 asymptomatic carriers and 18 patients with A-ATTRv. We did not find a higher prevalence of SIBO, among patients with A-ATTRv compared to asymptomatic carriers. Though no significant relationship between SIBO and A-ATTRv was found, notable differences in gastrointestinal symptoms suggest these may be independent of SIBO. Furthermore, no relationship was found between the presence of SIBO and gender. Given the limitations of this pilot study, we did not find a relationship between A-ATTRv and intestinal microbiota disorders. Future research with larger sample sizes and more sensitive diagnostic tools is required to further explore this potential link.